2001
DOI: 10.1067/mtc.2001.116201
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of primary lung cancer with synchronous brain metastases

Abstract: Although the overall survival for patients who have brain metastases from non-small cell lung cancer is poor, surgical resection may prove beneficial in a select group of patients with synchronous brain metastases and lung cancer without lymph node metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
4
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(135 citation statements)
references
References 27 publications
6
115
4
10
Order By: Relevance
“…13,14 Similarly, some studies found no survival difference according to nodal status, 5,20 whereas other studies demonstrate longer survival in lymph node negative patients compared with lymph node positive patients. 9,10 In this study age was also significant for survival in patients undergoing treatment of their brain metastases. On the basis of our results, we recommend that selected patients less than 65-years-old with stage I/II thoracic disease, who are eligible to undergo aggressive cranial treatment, should also be considered for radical thoracic treatment.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…13,14 Similarly, some studies found no survival difference according to nodal status, 5,20 whereas other studies demonstrate longer survival in lymph node negative patients compared with lymph node positive patients. 9,10 In this study age was also significant for survival in patients undergoing treatment of their brain metastases. On the basis of our results, we recommend that selected patients less than 65-years-old with stage I/II thoracic disease, who are eligible to undergo aggressive cranial treatment, should also be considered for radical thoracic treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Other authors have reported similar findings in selected patients, with OS ranging from 12.4 to 24 months, 1-year survival rates from 35% to 80%, and 5-year survivals from 25% to 70%. 4,9,10,14,[18][19][20] (Most studies reported that the prognosis of patients undergoing surgical resection for a synchronous BM from NSCLC mainly depended on the treatment of the lung tumor, with a survival advantage seen in patients receiving radical treatment (surgery or radiotherapy). 12,14,21 After SRS for solitary synchronous BM from NSCLC, a significantly longer OS (26.4 months) was similarly seen in patients who underwent radical thoracic treatment (surgery or chemoradiotherapy) than those undergoing palliative treatment (13.1 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Neurologically symptomatic patients have significantly shorter survival times than asymptomatic patients, as the median survival times have been estimated to be 4 and 7.5 months, respectively. 3 The optimal treatment for patients with neurologically symptomatic, synchronous (simultaneously having brain metastasis at the initial diagnosis), and multiple or solitary brain metastasis from NSCLC still remains controversial. Surgical resection of these metastatic lesions is considered in only 25% of patients.…”
Section: Treatment Options For Brain Metastasismentioning
confidence: 99%
“…Reported 5-year survival rates are 11-21.4%. Univariate analyses usually show a better prognosis for patients with adenocarcinoma, small pulmonary tumours and N0 disease [159,160].…”
Section: Surgery For Stage IV Lung Cancer (Solitary Metastasis)mentioning
confidence: 99%